Implementasi Pembentukan Karakter Siswa Usia Dini Di Paud Brigjend Katamso Medan Sunggal - Septy Yeremia Situmorang; Jean Emeninta Surbakti; Sartika Sartika; Syahrial Syahrial (Sekolah Tinggi Agama Islam Yayasan Pendidikan Ilmu Qur'an Baubau, 2024)
This research aims to determine the implementation/application of character building in Brigjend Katamso Medan PAUD students while at school. The results of the research show that the process of implementing or implementing children's character education begins as early as possible with habits such as (1) inviting students to pray diligently, (2) 3S, namely smile, greet, salute, (3) form independent character, (4) Obedience in the rules, (5) Healthy living behavior implemented by teachers at school so that students also practice it in their daily lives both at school, home and in the community.